Tingkat Maturasi in vitro Oosit Kambing dalam Medium dengan Suplementasi Serum dan Albumin - Gustari, Sri; Kurniani Karja, Ni Wayan; Rizky Amelia, Yuke; Kurniawan, Ian; Sulistyo, Bayu (Jurnal Veteriner; Vol 10 No 4 (2009), 2009)
The present study aimed to study the effect of ?maturation media? on maturation rate of goat oocytes after in vitro maturation. Goat ovaries were collected from a slaughter house in Godean, Sleman. Immediately after slaughter the ovaries were collected, rinsed with physiological NaCl three times then placed in a flask containing the NaCl solutions and hept at 36-370C before transportaion to the laboratory. Oocytes were observed under stereo microscope and its quality was classified into A, B, and C. Oocytes in vitro maturaion (IVM) was performed in TCM-199 media suplemented with : a) 0.4 mg/ml bovine serum albumin (BSA); and b) 10% newborn calf serum (NCS) then incubated at 38.50C with 5% CO2 for 24-27 h. Following this, oocytes were observed under inverted microscope for first polar body extrusion, then stained with aceto-orcein in order to evaluate nuck or maturation. The nuclear maturation stages including : germinal vesicles (GV), germinal vesicles break down (GVBD), metaphase I, apaphase I, telophase I and metaphase II, respectivelly. The overall results showed that 74-74%, 52-66.6% and 21.5-23.8% of oocytes quality A, B, and C reached maturation at metaphase II, respectivelly. There were no significant differences in oocytes maturation using media supplemented with either BSA or NCS.
Keywords: goat, oocytes maturation, in vitro fertilization